Cyclosporine-A mimicked the ischemic pre- and postconditioning-mediated cardioprotection in hypertensive rats: Role of PKCε - González Arbeláez, Luisa Fernanda (2016)
Our aim was to assess the action of cyclosporine-A (CsA) against reperfusion injury in spontaneously hypertensive rats (SHR) compared to the effects of ischemic pre- (IP) and postconditioning (IPC), examining the role played by PKCε. Isolated hearts were submitted to the following protocols: IC: 45 min global ischemia (GI) and 1 h reperfusion (R); IP: a cycle of 5 min GI and 10 min of R prior to 45 min-GI; and IPC: three cycles of 30 s-GI/30 s-R at the start of R. Other hearts of the IC, IP and IPC groups received CsA (mitochondrial permeability transition pore inhibitor) or chelerythrine (Che, non-selective PKC inhibitor). Infarct size (IS) was assessed. TBARS and reduced glutathione (GSH) content - as parameters of oxidative damage, the expression of P-Akt, P-GSK-3β, P-PKCε and cytochrome c (Cyc) release - as an index of mitochondrial permeability and the response of isolated mitochondria to Ca2+ were also measured. IS similarly decreased in preconditioned, postconditioned and CsA treated heart showing the highest values in the combinations IP + CsA and IPC + CsA. TBARS decreased and GSH was partially preserved after all interventions. The content of P-Akt, P-GSK-3β and P-PKCε increased in cytosol and decreased in mitochondria after IP and IPC. In CsA treated hearts these enzymes increased in both fractions reaching the highest values. Cyc release was attenuated and the response of mitochondria to Ca2+ was improved by the interventions. The beneficial effects of IP and IPC were annulled when PKC was inhibited with Che. A PKCε/VDAC association was also detected. These data show that, in SHR, the CsA treatment mimicked and reinforced the cardioprotective action afforded by IP and IPC in which PKCε-mediated attenuation of mitochondrial permeability appears as the main mechanism involved.